Treatment of post-dural puncture headache: current strategies and literature review - Osiak, Oliwia; Pękala, Maja; Niedziółka, Katarzyna; Ignatowicz, Jakub; Ochwat, Maria; Marczuk, Kinga; Nowak, Klaudia; Radomyska, Lidia (Journal of Education, Health and Sport, 2026)
Introduction and purpose Post-dural puncture headache (PDPH) is an iatrogenic complication of lumbar puncture and neuraxial procedures, characterized by an orthostatic headache that typically develops within 48–72 hours following dural puncture. The pathophysiology of PDPH is primarily associated with cerebrospinal fluid leakage, leading to decreased intracranial pressure, traction of pain-sensitive intracranial structures, and secondary cerebral vasodilation. The incidence of PDPH depends on patient-related factors as well as technical aspects of the procedure, with the highest risk observed in young women, particularly in the obstetric population. Diagnosis is based on the characteristic clinical presentation in temporal association with a recent neuraxial intervention. Management includes conservative and pharmacological approaches; however, in refractory cases, the epidural blood patch remains the most effective therapeutic intervention. Material and methods The literature available in Pubmed and Google Scholar databases was conducted using the key words. Results The literature review indicates that post-dural puncture headache remains a common complication following dural puncture procedures. Conservative management, including bed rest, hydration, caffeine administration, and analgesics, is often effective in mild cases. In patients with persistent or severe symptoms, interventional methods—most notably the epidural blood patch—demonstrate high efficacy and rapid symptom relief. Conclusions Post-dural puncture headache is a clinically significant condition that may substantially affect patient comfort and recovery. Current evidence supports a stepwise approach to treatment, beginning with conservative measures and progressing to interventional therapies when necessary. The epidural blood patch remains the gold standard for refractory cases.